EXPLORING THE 4CS IN PRACTICE: A STUDY OF CLIL IMPLEMENTATION IN A PRIMARY CLASSROOM - Marshalina, Afifah; Suryati, Nunung; Zen, Evynurul Laily (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2025)
In recent years, Content and Language Integrated Learning (CLIL) has gained increasing prominence as a pedagogical trend in many educational systems. The centerpiece of CLIL is the 4C framework- Content, Communication, Cognition, and Culture, which provides a foundation for conducting lessons that support language and subject learning. This study examined how the 4C was integrated into a science class that used English as the language of instruction among first-grade primary school students. The teacher’s lesson plan and classroom observations were used to gather data for this qualitative study design. Findings revealed that teachers were integrating the 4C into classroom teaching. Visual aids, language simplification, and repetition were provided to support content learning. Communication was fostered with the active use of language through classroom activities such as group work and hands-on experiments that could also engage students in cultivating thinking skills. Lastly, global examples that were pertinent to the subject matter were used to introduce cultural features. This study highlighted the potential of the 4C framework to be actualized among young learners. The implications of this study suggested the significance of deliberate planning to realize the CLIL principles in an integrated manner. Furthermore, this study showed that young learners can actively participate in cognitively and linguistically rich learning environments if provided with adequate support from teachers.